2014
DOI: 10.1039/c3fo60440c
|View full text |Cite
|
Sign up to set email alerts
|

The functional evaluation of waste yuzu (Citrus junos) seeds

Abstract: We have succeeded in extracting a large amount of expensive limonoids and the high total antioxidant capability yuzu seed oil from waste yuzu seed by simple methods. Yuzu seeds contain higher amounts of fat-soluble limonoid aglycone (330.6 mg g(-1) of dry seed), water-soluble limonoid glycoside (452.0 mg g(-1) of dry seed), and oil (40 mg g(-1) of green seed) than other citrus fruits. The antioxidant activities of yuzu seed aglycone, glycoside, and seed oil were evaluated in vitro. The potential antioxidant ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
16
1
Order By: Relevance
“…Bonaccorsi and co-workers [77,78] have reported that lemon and orange seeds contain as many limonoids as 375 and 114 mg/kg, respectively. These values were by far lower than those reported for lemon and orange seeds (18.93 and 22.33 mg/g dry seed, respectively) by other authors [79]. Noteworthy, a labor-intensive sample preparation protocol followed in the latter study probably resulted in higher extraction yields.…”
Section: Citrus Seedscontrasting
confidence: 68%
“…Bonaccorsi and co-workers [77,78] have reported that lemon and orange seeds contain as many limonoids as 375 and 114 mg/kg, respectively. These values were by far lower than those reported for lemon and orange seeds (18.93 and 22.33 mg/g dry seed, respectively) by other authors [79]. Noteworthy, a labor-intensive sample preparation protocol followed in the latter study probably resulted in higher extraction yields.…”
Section: Citrus Seedscontrasting
confidence: 68%
“…By using reversed-phase HPLC and LC-MS, four limonoid aglycones (1-4) and seven limonoid glucosides; 11-14, 49, 50, and ichangin glucoside (51, Figure 16) of the limonin group were identified from the yuzu seed extracts. Their amounts were found to be higher than those found in other citrus fruits [168]. The isolation and identification of both limonoids aglycones and glucosides by routinary HPLC and spectrometric or spectroscopic analyses is reported in several recent papers [48,52,169].…”
Section: Limonoid Aglycones and Glucosidesmentioning
confidence: 99%
“…In general, when compared to other citrus juices, the limonoid glucoside content in the sour orange juices is much lower than that of sweet oranges and, among the limonoid glucosides present, nomilin related glucosides, 13, 14, and deacetylnomilin 17-β-D-glucoside (50), were predominant [167]. Finally, in a project aimed at using renewable natural resources, Minamisawa et al [168] proposed in 2014 the extraction of large amounts of limonoids from waste yuzu (C. junos) seeds. By using reversed-phase HPLC and LC-MS, four limonoid aglycones (1-4) and seven limonoid glucosides; 11-14, 49, 50, and ichangin glucoside (51, Figure 16) of the limonin group were identified from the yuzu seed extracts.…”
Section: Limonoid Aglycones and Glucosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Citros junos fruit extract, known as yuzu, provides an important dietary source of anti-oxidant compounds with rich polyphenol and limonoid contents [82], and it has also anti-inflammatory properties [83,84].…”
Section: Discussionmentioning
confidence: 99%